Frontispiece: Photocatalytic CO2 Reduction on TiO2‐Based Materials under Controlled Reaction Conditions: Systematic Insights from a Literature Study. Issue 49 (3rd September 2018) - Moustakas, Nikolaos G.; Strunk, Jennifer
Abstract : Photocatalytic CO2 conversion to hydrocarbons (sometimes referred to as 'artificial photosynthesis'), which mimics natural photosynthesis with purely inorganic photocatalysts, has the potential to simultaneously combat the energy crisis and the greenhouse effect. In more than half of all reported studies to date, TiO2 ‐based materials are used as the photocatalyst. The Concept article by N. G. Moustakas and J. Strunk onpage 12739 ff., aims to give a guide for future research to obtain more efficient photocatalytic systems.